2020
DOI: 10.1097/md.0000000000021952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium cantharidinate/vitamin B6 injection on survival, liver function, immune function, and quality of life in patients with hepatocellular carcinoma

Abstract: Background: Sodium cantharidinate/vitamin B6 (SC/VB6) injection, a famous insect-derived traditional Chinese medicine preparation, has been widely applied as a promising adjunctive drug for hepatocellular carcinoma (HCC). However, its exact clinical efficacy and safety is still not well investigated. In this study, we aimed to summarize the efficacy of SC/VB6 injection on survival, liver function, immune function, and quality of life (QoL) in patients with HCC through the meta-analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Clinical studies have shown that SCA combined with hepatic artery perfusion have achieved significant efficacy in the treatment of patients with hepatocellular carcinoma (HCC) ( 16 ), and SCA injection was also approved by the China Food and Drug Administration in 2013 for HCC ( 17 ). Recent clinical ( 18 – 21 , 31 – 34 ) observations have found that SCA combined with chemotherapy exerted a significant synergistic effect in the treatment of esophageal, gastric, pancreatic and cervical cancer, osteosarcoma and other solid tumors, without increasing the incidence of adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that SCA combined with hepatic artery perfusion have achieved significant efficacy in the treatment of patients with hepatocellular carcinoma (HCC) ( 16 ), and SCA injection was also approved by the China Food and Drug Administration in 2013 for HCC ( 17 ). Recent clinical ( 18 – 21 , 31 – 34 ) observations have found that SCA combined with chemotherapy exerted a significant synergistic effect in the treatment of esophageal, gastric, pancreatic and cervical cancer, osteosarcoma and other solid tumors, without increasing the incidence of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer effects of SCA are mainly mediated by restricting cell cycle progression from the S phase to G/M phase in cancer cells, thereby inhibiting cell proliferation and inducing cell apoptosis, similar to the action of cytotoxic drugs ( 15 ). Clinical studies have shown that SCA combined with hepatic artery perfusion have achieved significant efficacy in the treatment of patients with hepatocellular carcinoma (HCC) ( 16 ), and SCA injection was also approved by the China Food and Drug Administration in 2013 for HCC ( 17 ). Recent clinical observations have found that SCA combined with chemotherapy exerted a significant synergistic effect in the treatment of esophageal, gastric, pancreatic and cervical cancer, osteosarcoma and other solid tumors, without increasing the incidence of adverse events ( 18 – 21 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2020 ; Zhu et al. 2020 ). If publication bias was detected, a trim-and-fill method was applied to coordinate the estimates from unpublished studies and the adjusted results were compared with the original pooled RR (Shi and Lin 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary search of the database yielded 262 Chinese and English articles. After removing duplicates, reading titles and abstracts, and detailing the full text, 12 studies [10][11][12][13][14][15][16][17][18][19][20][21] with a total of 1200 patients were finalized. Six hundred of them belonged to control group while 600 of them were in the test group (Fig.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Nine publications [10,12,[14][15][16][17][18][19]21] evaluated 24-hour UTP in the combination and control groups. After a test of heterogeneity (P < .00001, I 2 = 92%), we used a random-effects model.…”
Section: Meta-analysis Of the 24-hour Utp Levelmentioning
confidence: 99%